The Journalistic Treatment of the Phenomenon of Domestic Violence in Algerian Society A Content Analysis of El Khabar Daily Newspaper - Bendaoud , Larbi (Journal of Ecohumanism, 2025)
This article aims to explore how the Algerian print press addresses the phenomenon of domestic violence, taking El Khabar daily newspaper as a case study. Domestic violence is one of the most serious social issues, representing a form of aggressive behavior against society that threatens its security, stability, and integrity. The media institution, in all its forms, is considered one of the key social institutions that have a direct impact on the occurrence of domestic violence. Its importance lies in the way it reports and handles news related to this phenomenon.